Ownership structure and minority expropriation in Lebanon. (2016) - Azoury, Nehme; Bouri, Elie
This paper examines minority expropriation issues in the dominant presence of family ownership using longitudinal (hand-collected) data on 270 Lebanese non-financial firms between 2009 and 2012. The analysis reveals that family-related CEOs and the disparity between cash-flow rights and voting rights facilitate expropriation. However, the presence of private equity and banking firms reduces private benefit extraction. By explicitly focusing on the ownership-expropriation nexus and by promoting the development and implementation of a tailored governance code that considers Lebanese specificities, this paper makes a contribution to the growing literature on the role of corporate governance in emerging markets.